Calendar Anomalies in the Grains Futures Market - Karol WOJTOWICZ (Communications of International Proceedings, 2025)
Calendar anomalies are specific patterns in the price behavior of financial instruments that are associated with specific moments in time—days of the week, months, seasons, or periods of the financial year. Their existence contradicts, to some extent, the efficient market hypothesis (EMH), which holds that security prices should fully reflect all available information and therefore should not exhibit predictable patterns. Numerous studies demonstrate their presence in securities markets. Investor activity in commodity markets suggests the importance of verifying the presence of anomalies among commodity instruments. The grain futures market is a segment of the commodity market where futures contracts for grains such as wheat, corn, barley, oats, and rye are traded. Its primary function is to hedge price risk and shape expectations for future grain prices. Investors in derivatives markets are not interested in the actual delivery of goods - their transactions are in the nature of financial settlements, not through the actual transfer of grain. Financial investments in grain markets raise questions: Can anomalies characteristic of securities markets be identified in commodity futures markets? And can they form the basis of investment strategies that allow investors to achieve above-average rates of return? The main objective of the study is to identify calendar anomalies in the market of selected grains futures market. The following instruments were included in the study: Corn, Soybean Oil, Soybean Meal, Oats, Rough Rice, Soybean, Wheat. The research was conducted in 2015-2024. The study confirmed above-average rates of return during certain time periods. In the case of the day-of-the-week effect, investments made on Fridays were found to be the most profitable, while those made on Thursdays were found to be the least profitable. Regarding the week-of-the-month effect, the fourth week offered the greatest potential for profitability, as did the third week for short selling. An analysis of the month-of-the-year effect revealed that June and July offered the greatest investment potential for short selling. The research also shows that the highest (lowest) rates of return were achieved in the case of the month-of-the-year effect.
Keywords: market efficiency; grains; investment; calendar anomaly